Sergіy Оmelyanovуch Guryev - "USPC of Emergency Medical Care and Disaster Medicine", SE (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
The article is devoted to the 60th anniversary of the well-known scientist laureate of the State Prize of Ukraine in the field of science and technology, the Honored Doctor of Ukraine, Professor Guryev Sergіy Оmelyanovуch.